PENGARUH ENVIRONMENTAL COST, CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE, DAN OPERATING CASH FLOW TERHADAP EARNINGS MANAGEMENT (Studi Empiris pada Perusahaan Non Keuangan yang terdaftar di Bursa Efek Indonesia Periode 2021-2024) - Four Intan Juliana Sihotang; Dwi Ratmono (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the effect of environmental cost, corporate social responsibility (CSR) disclosure, and operating cash flow on earnings management practices, both in the form of accrual earnings management (AEM) and real earnings management (REM). This research is motivated by the increasing demand for corporate transparency in sustainability aspects, as well as indications that environmental and social activities may be used as a means of legitimacy or as an effort to enhance the transparency of financial reporting.The population of this study consists of all non-financial companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2024. The sampling technique used is purposive sampling based on specific criteria, resulting in a total of 126 firm-year observations that meet the research requirements. The data used are secondary data obtained from annual reports and sustainability reports of the companies. The analysis method employed is panel data regression analysis using Eviews 13 software.The results provide empirical evidence regarding the effect of environmental cost, CSR disclosure, and operating cash flow on earnings management practices. This study also contributes to enriching the literature on the relationship between corporate sustainability practices and the quality of financial reporting, particularly in non-financial companies in Indonesia.